Body-condition dynamics in a northern ungulate gaining fat in winter - Couturier, Serge; Côté, Steeve D.; Huot, Jean; Otto, Robert D. (Canadian Journal of Zoology, 2020)
Individual condition generally depends on density and is partly determined by habitat quality and climate. Westudied long-term trends in the condition and productivity of female caribou (Rangifer tarandus(L., 1758)) in two largemigratory herds in the Quebec–Labrador peninsula (Canada), the George and the Feuilles herds. Females from the Georgeherd were in better summer condition than those from the more abundant Feuilles herd in 2001–2002, while it was the op-posite in 1988 when the Feuilles herd was less abundant than the George herd. Summer nutrition followed the same pat-tern between herds through time. Spring body condition of females in the George herd declined from 1976 to the mid-1980s during early population growth. Fall condition, however, did not change from 1983 to 2002 when caribou numbersfirst peaked and later declined. Pregnancy rates were inversely related to herd size in both herds. Vegetation quality(NDVI) in June was significantly related to body proteins in the fall. Albeit unusual for a northern ungulate, body fat in-creased from fall to spring in the George herd. We conclude that a relatively small and highly grazed summer range, aswell as density-dependent effects, affected summer nutrition and the need to continue lipogenesis during winter. La condition physique des animaux dépend généralement de la densité de la population et est partiellement déterminée par la qualité de l’habitat et le climat. Nous avons étudié les variations à long terme de la condition corporelle et de la productivité des femelles du caribou (Rangifer tarandus (L., 1758)) dans deux grands troupeaux migrateurs de la péninsule du Québec–Labrador, les troupeaux George et Feuilles. Les femelles du troupeau George étaient en meilleure condition estivale que celles du plus grand troupeau Feuilles en 2001–2002, tandis que le contraire s’observait en 1988 alors que le troupeau Feuilles était moins abondant que le troupeau George. La nutrition estivale a suivi le même patron temporel chez les deux troupeaux. La condition ...